Wpływ składu gatunkowego drzewostanów na cechy jakościowe próchnicy glebowej tworzącej się na zrekultywowanym wyrobisku popiaskowym = Influence of tree species composition on qualitative properties of soil humus formed on reclaimed sand mine excavation - Woś, Bartłomiej; Pietrzykowski, Marcin; Pająk, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents influence of tree species composition on qualitative properties of humus in soil developed on reclaimed and afforested sand mine excavation KP Szczakowa. Fractional composition and optical properties were determined on 16 samples collected from top soil layer (0-5 cm) under different species: pure stands of Scots pine, European larch, common birch and black alder. The examined humus were generally characterized by predominance of fulvic acids (CKf) in relation to humic acids (CKh) and relatively low optical density of humic acid (E465/E665).
Keywords: zalesienie; glebowa materia organiczna; kwasy fulwowe; kwasy huminowe; gęstość optyczna; afforestation; soil organic matter; fulvic acid; humic acid; humus optical density